Ferrock: A Carbon Negative Sustainable Concrete - M, Niveditha; Manjunath, Y M; Prasanna, Setting H S (International Journal of Sustainable Construction Engineering and Technology, 2021)
In this fast-growing world, people are focusing on the infrastructural development, where construction sector plays an important role. Cement is the most prominent material being used in construction that emits approximately 6-8% of the total carbon dioxide in the world during its production which is the major constituent of global warming. Thus, focusing on the carbon emission reduction and also utilization of the waste products for a better environment, a product named Ferrock was constituted. This paper is a review over a product that is stepping towards carbon negativity and waste management. It shows the best usage of iron ore waste powder obtained during the mining process that is just dumped away from the mines, causing air pollution, health hazards and also consuming larger area. The product indirectly reduces the carbon dioxide released by its unique strength gaining mechanism, which is in contrary with that of the cement and thus stands out among many other supplements of cement. Ferrock involves a curing process with carbonation and air curing in varied number of days for better strength in terms of compression, tensile strengths and achieving desirable properties. Ferrock is thus a more promising eco friendlier binding material in terms of its carbon negativity and in best usage of the waste.